Partial Characterization of Endogenous Modulators of Muscarinic Acetylcholine Receptors in Human Frontal Cortex - Loureiro-Dos Santos, Nelson Enrique; Rodríguez-Valenzuela, Carla Silvia; Bonfante-Cabarcas, Rafael Armando; Pascuzzo-Lima, Carmine; Moreno-Yanes, José Antonio (Investigación Clínica, 2009)
<!–[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!– /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> A soluble fraction from human frontal cortex with molecular weight less than 10 kD was tested for the presence of endogenous substances capable of modulating the [3H]-QNB binding to crude P1 + P2 fractions from the same region. The soluble fraction was able to decrease [3H]-QNB binding in a dose-response manner with an IC50 of about 30 Âµg/ml. The effect appeared to be noncompetitive in nature, since Bmax but not Kd was significantly affected; however, in some specimens a biphasic profile, with an initial inhibition of 88-90% of [3H]-QNB binding and 50-60% ulterior binding recuperation was also found. The modulator appeared to have a molecular weight less than 10,000 Daltons and was heat and trypsin resistant. These results point out the existence of an endogenous factor, which could be heterogeneous in regard to its molecular nature or to its action sites